2023
DOI: 10.1111/jpn.13859
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of lipid digestion and absorption in poultry: An updated review on the supplementation of exogenous emulsifiers in broiler diets

Elijah O. Oketch,
Samiru S. Wickramasuriya,
Sungtaek Oh
et al.

Abstract: Lipids are a concentrated source of energy with at least twice as much energy as the same amount of carbohydrates and protein. Dietary lipids provide a practical alternative toward increasing the dietary energy density of feeds for high‐performing modern broilers. However, the digestion and absorption of dietary lipids are much more complex than that of the other macronutrients. In addition, young birds are physiologically limited in their capacity to utilise dietary fats and oils effectively. The use of dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…Several reports have shown that fermented diet by probiotics can produce more organic acids and release other metabolite, which is effective in maintaining the balance of the gastrointestinal tract of livestock and poultry and enhancing the feed conversion rate and the body immunity ( Xu et al, 2020 ; Chang et al, 2023 ). In addition, fermentation diets produced a variety of bio-active substances which was possessed the antimicrobial, antioxidant, degradation of mold toxins, decomposition of anti-nutritional factors and other functions ( Basson et al, 2020 ; Oketch et al, 2023 ). Therefore, in this study, we firstly investigated that the effects of FF with Muscovy duck's compound probiotics on feed nutrient levels, such as lipid and protein metabolites, the results found that Muscovy duck's compound probiotics co-fermentation increased the concentrations of FA in fermented diets, and significantly improved the numbers of short peptide in diets, this also accords with earlier observations that microbial fermentation has increased the concentrations of FA, which was a class of easily absorbed small molecule nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that fermented diet by probiotics can produce more organic acids and release other metabolite, which is effective in maintaining the balance of the gastrointestinal tract of livestock and poultry and enhancing the feed conversion rate and the body immunity ( Xu et al, 2020 ; Chang et al, 2023 ). In addition, fermentation diets produced a variety of bio-active substances which was possessed the antimicrobial, antioxidant, degradation of mold toxins, decomposition of anti-nutritional factors and other functions ( Basson et al, 2020 ; Oketch et al, 2023 ). Therefore, in this study, we firstly investigated that the effects of FF with Muscovy duck's compound probiotics on feed nutrient levels, such as lipid and protein metabolites, the results found that Muscovy duck's compound probiotics co-fermentation increased the concentrations of FA in fermented diets, and significantly improved the numbers of short peptide in diets, this also accords with earlier observations that microbial fermentation has increased the concentrations of FA, which was a class of easily absorbed small molecule nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics have been reported to improve feed intake and utilization; stimulate immune response; and promote mucosal integrity [ 2 , 4 , 6 ]. These benefits contribute to improved gut health, i.e., the general presence of a stable and coordinated interaction between the diet, commensal microbiome, intestinal mucosa, and immune system in a symbiotic equilibrium that allows the gut to perform physiological functions, self-regulate, and withstand stressors [ 18 ]. Specifically, the efficacy of supplemental Bacillus subtilis PB6, Bacillus subtilis FXA, and Bacillus licheniformis G3 to increase the productive performance and egg quality; modulate the mechanism behind mineral absorption and bone mineralization; and improve the intestinal microbial balance of layers was investigated at two different levels.…”
Section: Discussionmentioning
confidence: 99%
“…Where the cost and demand for increased energy in feed meals to meet the requirements of fast-growing birds has become the subject of attention of nutritionists, as dietary fats are one of the preferred ways to achieve this purpose, as various sources of fat have been introduced in poultry nutrition, including animal fats such as cow fat, lard, poultry fat, vegetable oils such as Linseed oil, soybean oil, corn oil, palm oil and sunflower oil [9]. In addition to the high energy density that is almost twice the same amount of carbohydrates and proteins, fats and edible oils are relatively inexpensive compared to corn, so the use of dietary fats provides a reasonable alternative to increase the energy density in the diets of modern high-performance broilers at relatively low costs [10]. Commercial broilers are characterized by a short production cycle and high energy requirements, so adding fats to their diet is a must as fats and oils contain the highest level of calories among all nutrients [11].…”
Section: Introductionmentioning
confidence: 99%